COMMUNITY-BASED TOURISM DEVELOPMENT IN TOBA SAMOSIR REGENCY - Maylana; Ti. Aisyah; Arinanda; Ferizaldi; Murniati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Lake Toba, as a super-priority destination in Indonesia, has tremendous tourism potential. The development of community-based tourism (CBT) is a key strategy to ensure that its benefits are felt directly by the local community. However, its implementation in Toba Regency still faces significant challenges, including economic disparities, suboptimal community empowerment, and environmental sustainability issues, so that there is a gap between expectations and the reality received by the community. This study aims to examine in depth the development of Community Based Tourism in Toba Regency. The focus of the study is twofold: first, identifying social and economic programs that have been running; second, analyzing the main factors that hinder the effectiveness of tourism development. This study uses a descriptive qualitative approach. Data were collected through in-depth interviews with key informants from the Lake Toba Authority Implementing Agency, local government, community, and tourists, who were selected through purposive and accidental sampling techniques. Data were also obtained from observations and documentation studies, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that social programs (craft training, guides, homestays) and economic programs (business groups, capital facilitation) have been running, but their reach and benefits are not evenly distributed. The main obstacle identified is the deficit of social capital, which is characterized by low trust and cohesion between residents, and weak coordination between stakeholders. In addition, limited capacity and technical skills of the community in tourism business management are also significant obstacles. Optimizing the potential of Lake Toba requires a more integrated approach.